2003
DOI: 10.1002/jctb.871
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic removal of hexavalent chromium from aqueous solutions

Abstract: The removal of hexavalent chromium from a synthetic solution and from an industrial sample by electrolysis using stainless steel plate and titanium mesh cathodes is studied. It is found that the process proceeds in two steps: (1) electroreduction of hexavalent chromium to trivalent chromium in highly acidic medium and (2) electrochemical precipitation of trivalent chromium in an alkaline medium. A comparative study of electroreduction, electrochemical reduction and chemical reduction of hexavalent chromium is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 18 publications
3
46
0
Order By: Relevance
“…They reported that 100% Cr reduction took place from synthetic water, while 94-99% was true for tannery water after 2 h electrolysis. Other workers [14] have also described the electrolytic removal of hexavalent chromium from a synthetic solution and from an industrial sample, but they used stainless steel plate and titanium mesh cathodes with a two-steps strategy: (1) electro-reduction of Cr(VI) to Cr(III) in highly acidic medium and (2) electrochemical precipitation of Cr(III) in an alkaline medium. According to their observation, electro-reduction is a clean technology as compared to chemical reduction.…”
Section: Introductionmentioning
confidence: 98%
“…They reported that 100% Cr reduction took place from synthetic water, while 94-99% was true for tannery water after 2 h electrolysis. Other workers [14] have also described the electrolytic removal of hexavalent chromium from a synthetic solution and from an industrial sample, but they used stainless steel plate and titanium mesh cathodes with a two-steps strategy: (1) electro-reduction of Cr(VI) to Cr(III) in highly acidic medium and (2) electrochemical precipitation of Cr(III) in an alkaline medium. According to their observation, electro-reduction is a clean technology as compared to chemical reduction.…”
Section: Introductionmentioning
confidence: 98%
“…This process offers detoxification without chemical reducing agents, minimization of salt freight and a lower sludge production. This technology has been under investigation for many years using either planar electrodes [1][2][3][4], mesh type electrodes [3,5] or packed beds with granular carbon [6][7][8][9]. Ibl and Frei [4] reported promising results with two-dimensional electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…These facts can be used for MWCNT as a carbonaceous material and are shown in Equations 4-6. Also, adsorption decrease at higher pH (pH > 5) are expressed due to the formation of soluble hydroxilated complexes (19 …”
Section: Discussionmentioning
confidence: 99%